Multi-Risk Governance of Solar Radiation Modification - Jonathan B. Wiener; Tyler Felgenhauer; Mark E. Borsuk (European Journal of Risk Regulation)
Solar radiation modification (SRM) presents important challenges to risk regulation and governance, arising from the array of multiple risks that SRM may influence. SRM would not simply reverse climate change, but could pose further ancillary impacts, depending on the method of SRM, such as stratospheric aerosol injection (SAI), marine cloud brightening (MCB), or a space-based planetary sunshade system (PSS). We identify multiple risks that SRM may influence, both biophysical and sociopolitical, to be compared to the multiple risks that may be affected by greenhouse gas (GHG) mitigation and climate adaptation. This multi-risk framework helps analysts and decision makers identify, evaluate, and compare multiple risks holistically; helps identify affected groups to overcome problems of disregard and omitted voice; helps compare policy options and map the array of risks to corresponding (or missing) governance mechanisms; and seeks risk-superior policies that would reduce multiple risks in concert. We then examine governance frameworks: uncoordinated, coordinated and comprehensive. We suggest two key mechanisms that can help build up from uncoordinated toward more coordinated or even comprehensive approaches, and that can gain support from SRM advocates, observers and critics alike: a series of international assessments of SRM, and a transparent international monitoring system for SRM.